Mapping Risk Factors Associated with Breast Engorgement Among Postpartum Mothers: A Scoping Review - Neng Resi Fitriani; Johanes Cornelius Mose; Mochamad Rizkar Arev Sukarsa; Dwi Prasetyo; Sri Endah Rahayuningsih; Ruswana Anwar; Qorinah Estingtyas Sakilah Adnani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Cognitive decline is an increasing public health concern among older people, particularly Breast engorgement is one of the most common postpartum breastfeeding problems and may increase the risk of mastitis, maternal discomfort, and early breastfeeding discontinuation. This scoping review aimed to map and synthesize existing evidence regarding risk factors associated with breast engorgement in postpartum women. The review followed the PRISMA-ScR guidelines. A systematic search of Google Scholar, ScienceDirect, Wiley Online Library, and PubMed was conducted for articles published between 2015 and 2025. Studies examining factors associated with breast engorgement among postpartum mothers were eligible. Two independent reviewers performed study screening and selection, and data were charted using a standardized extraction form. A total of 11 articles met the inclusion criteria and were included in the final analysis. The findings indicate that breast engorgement is a multifactorial condition influenced by maternal characteristics, socioeconomic and environmental factors, infant-related factors, breastfeeding practices, maternal knowledge and perceptions, family and social support, healthcare system support, and cultural practices. The themes were generated through inductive thematic analysis of the included studies. Recurrent patterns across studies suggest that inadequate milk removal, delayed breastfeeding initiation, limited maternal knowledge, and insufficient professional support are frequently reported factors associated with breast engorgement. This review highlights the complexity of breast engorgement and the broad range of factors discussed in the literature. The findings provide an evidence map that may inform future research, clinical practice, and supportive breastfeeding interventions, while acknowledging that scoping reviews are designed to explore and map evidence rather than determine causal relationships Keywords: Breast engorgement, postpartum mothers, breastfeeding, risk factors, scoping review